Capital Market Reaction to The Tax Amnesty Policy (Study on Banking Sector Share in Indonesia) - Gebby Aldhepis; Dominicus Savio Priyarsono; Trias Andati (Jurnal REKOMEN (Riset Ekonomi Manajemen), 2022)
An event or a policy taken by the government can be one of the considerations for investors in making investment decisions in a country. The existence of these events certainly contains information that can be interpreted to carry out transactions in the capital market. The tax amnesty policy is assumed to contain information that is able to respond to capital market players. The reaction of capital market participants can be measured by abnormal returns and trading volume activity. Therefore, it is necessary to conduct research on the reaction of the capital market to the tax amnesty policy in Indonesia on shares in the banking sector because banks are the gateway for the entry of tax amnesty funds. There are 14 bank shares included in the study that fall into the criteria of government perception banks and have IPOs. This study uses the event study analysis method with an observation period of 11 days, namely t-5 to t+5 and t0 as event dates in all tax amnesty policy periods, period I (1 July 2016), period II (1 October 2016), period III (1 January 2017). The research analysis technique used a paired sample t test. The results of the study indicate that there is a reaction in banking stocks to the tax amnesty policy which can be seen from the significant positive difference between the cumulative average abnormal return before and after the tax amnesty policy period I and II, as well as the difference in cumulative average trading volume activity between before and after the tax amnesty policy period I, II, and III. The results of the study conclude that the tax amnesty policy has succeeded in increasing trading activities and providing abnormal returns to investors for two periods on banking stocks so that this issue provides meaningful information and is good news for investors.